Conceptual comparison of three novel configurations in the spherical radial flow reactor for ammonia production. (1st August 2022) - Nikzad, Amin; Iranshahi, Davood; Ranjbaran, Mohammad; Bagherpour-Ardakani, Esmaeel
Highlight: Improvement in the chemical equilibrium of the gas phase reaction. Configurations were simulated based on momentum, energy, and mass balance equations. A two-dimensional pseudo- homogeneous model was developed. CFD simulation of spherical packed bed reactor is introduced for ammonia synthesis. Enhancement in the production rate of ammonia. Abstract: Since ammonia is a powerful energy carrier of hydrogen, the attempts are considered to improve the ammonia synthesis process. Reactors are the heart of chemical units. Because of the effect of pressure on gas phase and equilibrium reactions and significant pressure drop in tubular reactors, Spherical reactors are a good alternative. Due to the importance of fluid flow in reactors, 2-dimensional ammonia tubular and three configuration of spherical radial flow reactors were simulated with computational fluid dynamics (CFD) in the present study. The tubular reactor results are verified with experimental data at the same condition to justify the suggested model accuracy. The advantages of the proposed configurations are the possibility of using a higher flow rate and less pressure drop compared to the tubular configuration. The three proposed configurations include spherical reactors with four feed inputs (Config 4F), six feed inputs (Config 6F), and eight feed inputs (Config 8F). The simulation results also show that the nitrogen conversion rate in each recommended configuration has improved by 20.96%, 20.28%, and 19.66%, respectively. The spherical radial flow reactor with four feed inlets has the best performance among the provided configurations. Furthermore, the effect of process parameters, including flow scale-up ratio and outlet temperature of intermediate coolers, on the conversion of nitrogen has been investigated.